THE RELATIONSHIP BETWEEN KNOWLEDGE OF EATING AND SLEEPING PATTERNS AND THE INCIDENCE OF ANEMIA AND LEARNING ACHIEVEMENT - Titin Suhartini; Fanni Hanifa (CV Naskah Aceh, 2026)
Anemia is a condition in which the body experiences a decrease in the number of red blood cells, which falls below the normal range. This occurs due to a lack of hemoglobin (iron-rich protein), which affects the production of red blood cells. A deficiency in red blood cells causes fatigue and memory problems, which in students can affect their concentration while studying. Over the last three years, the incidence of anemia at MA S Ibnu Abbas school has consistently increased. Therefore, the purpose of this study is to determine the relationship between eating patterns, sleeping patterns, the occurrence of anemia, and academic achievement at MA S Ibnu Abbas Pulo Panjang. The research method used is quantitative with a cross-sectional approach. The population and sample used were 71 students of MA S Ibnu Abbas. Data analysis techniques included univariate and bivariate analysis (Chi-square). The results showed a significant relationship between eating patterns and sleeping patterns with the occurrence of anemia. There was also a significant relationship between eating patterns, sleeping patterns, and academic achievement. Furthermore, a significant relationship was found between the occurrence of anemia and academic achievement. It can be concluded that the occurrence of anemia at MA S Ibnu Abbas is influenced by eating and sleeping patterns, which also affect the students' academic performance.